PARTISIPASI WANITA TANI DALAM USAHATANI PADI (Oryza sativa L) SAWAH DI DUSUN TEGAL ANYAR DESA LOA JANAN ULU KECAMATAN LOA JANAN KABUPATEN KUTAI KARTANEGARA (Participation of Women Farmers in Rice Farming (Oryza sativa L) Rice Fields in Tegal Anyar Hamlet, Loa Janan Ulu Village, Loa Janan District, Kutai Kartanegara Regency) - EKO HARRI YULIANTO ARIFIN; OKY SETIA PRANAJAYA (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2022)
The woman farmer has a significant role in supporting the welfare of the management of farming and household businesses, but it was also related to the involvement of the wife who participates in helping her husband's income as head of the household. The purpose of this study was to determine the level of participation of women farmers in rice farming (Oryza sativa L.) rice fields in Tegal Anyar Hamlet, Loa Janan Ulu Village, Loa Janan District. This research was conducted from February to June 2021. The research location was in Tegal Anyar Hamlet, Loa Janan Subdistrict.Samples were taken using a purposive method with a total sample of 35 respondents. Data collected in this study are primary and secondary data. The data collection method is done by observation and direct interview with the respondent. Data analysis uses a Likert scale.The results showed that the participation of women farmers in rice farming (Oryza sativa L.) in Tegal Anyar Hamlet, Loajanan Ulu Village, Loa Janan District was included in the "Low" category. Farmer women only participate in the stages of planting and post-harvest activities.Based on the results of research and data processing and analysis, it was concluded that the participation of women farmers in the field of rice farming in Dusn Tegal Anyar Loa Janan Ulu Village Loajanan District only occurred in Planting and Post Harvesting so the participation rate was included in the "Low" category.